2017
DOI: 10.3382/ps/pew205
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of dietary arginine requirements for Longyan laying ducks

Abstract: This study aimed to establish the arginine requirements of Longyan ducks from 17 to 31 wk of age based on egg production, egg quality, plasma, and ovarian indices, as well as the expression of vitellogenesis-related genes. In total, 660 Longyan ducks with similar body weight at 15 wk of age were assigned randomly to 5 treatments, each with 6 replicates of 22 birds, and fed a corn-corn gluten meal basal diet (0.66% arginine) supplemented with either 0, 0.20%, 0.40%, 0.60%, or 0.80% arginine. Dietary arginine di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The breeders were then stunned, exsanguinated and the ovaries were collected and weighed. Samples were collected from the liver, oviduct magnum and ovaries ( 23 , 24 ) , which were rinsed rapidly with PBS, snap-frozen in liquid N 2 and stored at −80°C. After hatching, twelve ducklings from each treatment group (two ducklings from each replicate) were stunned, exsanguinated and samples of the liver and brain ( 25 ) were harvested, rinsed quickly with PBS, snap-frozen in liquid N 2 and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…The breeders were then stunned, exsanguinated and the ovaries were collected and weighed. Samples were collected from the liver, oviduct magnum and ovaries ( 23 , 24 ) , which were rinsed rapidly with PBS, snap-frozen in liquid N 2 and stored at −80°C. After hatching, twelve ducklings from each treatment group (two ducklings from each replicate) were stunned, exsanguinated and samples of the liver and brain ( 25 ) were harvested, rinsed quickly with PBS, snap-frozen in liquid N 2 and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Arg) in broiler feed increased the egg production and egg weight. Similarly, the study of Xia et al (2016) found that the supplementation of 1.26% (dig. Arg) L-Arginine in the feed of Longyan ducks increased the egg weight and egg yolk percentage.…”
Section: Introductionmentioning
confidence: 85%
“…Therefore, it is very difficult to compare our findings with others. However, increasing the levels of Arginine (an essential amino acid) in laying ducks diets from 17 to 31 wk did not affect the levels of E2, LH, or FSH hormone, whereas the concentration of P4 decreased and the number of small follicle increased (Xia et al 2017). Also, Meng et al (2016) observed that increasing the concentrations of methionine (the first limiting amino acid in poultry diets) from 0.26% to 0.39% in Chinese laying hens diets during grower phase significantly declined the concentrations of LH and FSH in serum and the account of large and small follicles.…”
Section: Egg Qualitymentioning
confidence: 99%
“…Five millilitres of blood was collected from the wing vein using heparinized tubes. Blood was centrifuged at (1200 × g) at 4°C for 10 min to harvest plasma, then plasma was stored at −20°C until estradiol (E2), luteinizing hormone (LH), follicle-stimulating hormone (FSH), and progesterone (P4) (reproductive hormones) determined as mentioned by Xia et al (2017).…”
Section: Blood Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation